2022
DOI: 10.1007/s00246-022-02909-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Plasma Copeptin Level in Children with Acute Heart Failure

Abstract: We investigated the ability of copeptin level to predict adverse outcome in pediatric heart failure (HF) and correlated copeptin level with various clinical and echocardiographic data. This cohort study was carried out on forty children with clinical picture of acute HF as the patient group and forty healthy children of matched age and sex as the control group. Echocardiographic examination and plasma copeptin level were performed for all included children at admission. Patients were followed up for 6 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Interestingly contrast to adult studies, copeptin levels were not significantly elevated in children with sepsis and septic shock compared to healthy controls [33,34]. Similar to our observations, Amrousy et al have reported copeptin level as an excellent prognostic value to predict adverse outcomes in pediatric heart failure [26]. However, they did not compare the predictive value of copeptin levels with BNP levels and the echocardiography variables of left ventricular function.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Interestingly contrast to adult studies, copeptin levels were not significantly elevated in children with sepsis and septic shock compared to healthy controls [33,34]. Similar to our observations, Amrousy et al have reported copeptin level as an excellent prognostic value to predict adverse outcomes in pediatric heart failure [26]. However, they did not compare the predictive value of copeptin levels with BNP levels and the echocardiography variables of left ventricular function.…”
Section: Discussionsupporting
confidence: 50%
“…Pediatric data on copeptin level as a predictor of adverse outcomes are limited to few studies, including arterial hypotension in critically ill children, pulmonary hypertension, ventricular dysfunction with vaso-occlusive crises of sickle cell anemia, and pediatric acute heart failure [25,26,[31][32][33]. Gaheen et al showed that copeptin levels were elevated in children with pulmonary hypertension secondary to congenital heart disease [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations